Factores de riesgo y enfermedad mental en estudiantes de enfermería de la Universidad Nacional De La Amazonía Peruana Iquitos 2023 - Escalante Espinoza, Christiam Pedro (2024)
The objective was to determine the association between risk factors and mental illness in Nursing students of the National University of the Peruvian Amazon Iquitos 2023, the type of research was quantitative, descriptive, correlational; the design was non-experimental, cross-sectional; The target population was 360 students and the sample was 186, the Chi-square statistical test was applied; The instruments were the Risk Factor Registration Form, Rosemberg Self-Esteem Scale and Symptom Questionnaire (SRQ); The main findings were; There is a statistically significant association between risk factors, young age and absence of anxiety (p=0.001); female gender and absence of anxiety (p=0.000) and absence of depression (p=0.008); child abuse and absence of anxiety (p=0.001), absence of depression (p=0.008); no drug use and absence of anxiety (p=0.007), absence of depression (p=0.001) and no risk of alcoholism (p=0.000); high self-esteem and absence of anxiety (p=0.000) and absence of depression (p=0.000 ); There is no statistically significant association between young age and absence of depression (p=0.114), being a case of psychosis (p=0.100) and without risk of alcoholism (0.104); female gender and being a case of psychosis (p=0.813), and without risk of alcoholism (p=0.140); suffering child abuse and being a case of psychosis (p=0.406), and without risk of alcoholism (p=0.218); not using drugs and being a case of psychosis (p=0.466); high self-esteem and being a case of psychosis (p=0.454), and no risk of alcoholism (p=0.067); concluding that most risk factors are associated with the absence of mental illness, except in psychosis, in the population studied.